Role of Identities in the Indo-Pak Relations: A Study in Constructivism - Anas Bin Tariq; Hamza Asim (Journal of Nautical Eye and Strategic Studies, 2023)
From the vary onset, the history of Pakistan and India is replevied with number of protracted conflicts. The antagonism and the animosity between the two states are generally viewed through the lens of realist paradigm. However, this research makes a radical departure from the realist precepts and lays considerable importance to the role of the social institutions in the formation of the conflictual relations between the two countries. The research undertakes an extensive study of the social institutions in the formation of a hostile identity between the two neighbors’. This research has unraveled that the social institutions of education, media, religion and politics have played an imperative role in the formation of interstate adversarial identities. It has been seen that the norms and ideas entailed in social institutions, has deliberately created and fostered the identity of conflicts between the two countries.